What is the effectiveness of structured lifestyle interventions (diet, exercise, sleep hygiene) in preventing relapse among adults with recurrent major depressive disorder ? : A Systematic Review - Ratu Qurroh' Ain; Melsha Syarahhandi; Melati Rosa Sitorus; Yudi Dwi Atmanto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Major Depressive Disorder (MDD) is a recurrent condition where preventing subsequent episodes is a primary clinical goal. While various non-pharmacological strategies exist, the evidence for structured lifestyle interventions in preventing MDD relapse is notably heterogeneous. This systematic review aims to evaluate the effectiveness of structured diet, exercise, and sleep hygiene interventions in preventing relapse among adults with recurrent MDD. Methods: This systematic review adhered to PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Semantic Scholar, Springer, Google Scholar, and Wiley Online Library for studies published since 2015. We included randomized controlled trials, meta-analyses, and prospective cohort studies that assessed non-pharmacological lifestyle interventions in adults with a history of at least two MDD episodes, with relapse/recurrence as a primary outcome. A total of 22 studies were included in the final synthesis. Results: The evidence base was varied. Psychological interventions demonstrated the strongest and most consistent evidence for reducing relapse risk, with meta-analyses reporting hazard ratios around 0.60. Dietary interventions, primarily the Mediterranean diet, improved depressive symptoms but did not consistently show a significant reduction in relapse rates. Combined lifestyle and exercise interventions were promising, particularly when patient adherence was high, with one multi-component study showing a relapse rate of 7.4% versus 25.3% in the control group. Conclusion: Based on the comprehensive analysis, the most significant finding is the clear distinction in efficacy among non-pharmacological interventions for preventing Major Depressive Disorder relapse. Psychological interventions, particularly those grounded in mindfulness and cognitive therapy, stand out with the most robust and consistent evidence, establishing them as a reliable strategy for reducing relapse risk. In contrast, while specific lifestyle modifications like diet and exercise are significant for improving symptoms, their direct impact on relapse prevention is less definitive and highly conditional upon sustained patient adherence.